The Disciples' Lack of Comprehension in the Gospel of Mark - Hur, Unsok (Biblical theology bulletin, 2019)
This article begins with William Wrede's (1901) suggestion that the writer of the Gospel of Mark added the scene of Jesus predicting his crucifixion and the text indicating that even when Jesus predicts his death his disciples remain unaware of that prediction. I agree with Wrede. Moreover, I argue that several passages describing the disciples' ignorance throughout Mark's Gospel are the creation of the Marcan gospel writer in order to make sense of the disciples' ignorance when Jesus predicts his death. The prime example is that when Jesus performed the second miracle of the loaves and fishes, they had totally forgotten the first miracle of the loaves and fishes. To conclude the article, I argue that the disciples' lack of comprehension described in Mark can be understood as fictional. That is, the description of the disciples in Mark differs from how the disciples actually acted historically. Unlike what is described in Mark, I argue that at the time of Jesus' crucifixion, the disciples neither ran away from Jesus nor lost faith in Jesus, but they had unwavering trust in him.